New epistemological challenges in biographical research in ‘Postmodernity’ - Alheit, Peter (Adult Education Discourses, 2020)
The following article deals with the problem of a dramatic change of the modern ‘subject code’. Modernity has changed. The magic of individuality, the autonomy of the subject that successfully opposes the class conventions of pre-modernity has probably become a myth and perhaps turned into a compulsion to be ‘singular’ in late modernity, as Andreas Reckwitz points it. We rediscover new dimensions of ‘subjectivisation’ and ‘governmentality’, as Michel Foucault identified it decades before. And we are even reminded of Pierre Bourdieu’s polemical thesis that the idea of a consistent biography is a pure illusion. Has ‘modern subject’ lost its importance? Is there no way out from this perspective? The article closes with a ‘skeptical optimism’.